ANALISIS PENCATATAN DAN PELAPORAN PAJAK HOTEL (STUDI PADA DISPENDA BITUNG DAN DISPENDA MANADO) - Kumaat, Mentari G.; Pangemanan, Sifrid S.; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2017)
Taxes are one source of state revenue. Local tax is a tax which is entrusted by the central government to be levied and managed by local governments. Local tax is one sector in incereasing local revenue. Hotel taxes included in the tax area. Hotel tax is a potential sector in raising revenue. The purpose this study to know the recording and reporting of hotel tax (study on Dispenda Bitung and Dispenda Manado). The method used is descriptive analysis, the research conducted by collecting data, analyzing the data collected, as well as giving particular faced, and draw conclusions. The data used in this research is secondary data, using all the data obtained from the source. The result show Dispenda Bitung and Dispenda Manado has yet to make its accounting records or journal transaction taxes when receiving payments of hotel taxes, and based on data from the Budget Realization Statement of hotel tax, hotel tax revenue of Manado city is greater than the hote tax revenue of Bitung city.Â Keywords : analysis, recording and reporting, hotel tax